2021
DOI: 10.1371/journal.pone.0250067
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serial neutrophil-to-lymphocyte ratio measurements in hospitalized community-acquired pneumonia

Abstract: Introduction Several serum inflammatory markers are associated with poor clinical outcomes in community-acquired pneumonia (CAP). However, the prognosis and early treatment response in hospitalized CAP patients based on serial neutrophil-to-lymphocyte ratio (NLR) measurement has never been investigated. Methods We performed a retrospective observational study for 175 consecutive patients hospitalized with CAP between February 2016 and February 2018. NLR, C-reactive protein (CRP) and procalcitonin levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It is characterized by high rates of mortality and morbidity, especially in elderly patients. NLR has demonstrated a strong predictive value concerning short- and long-term mortality, need for ICU admission and re-hospitalization [ 24 , 25 , 26 , 27 , 28 ]. Therefore, NLR correlated with post-CAP mortality better than traditional pneumonia scores (Pneumonia Severity Index, PSI; and Confusion, Urea, Respiratory rate and Blood pressure, aged 65 and older, CURB-65), WBC and CRP [ 24 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…It is characterized by high rates of mortality and morbidity, especially in elderly patients. NLR has demonstrated a strong predictive value concerning short- and long-term mortality, need for ICU admission and re-hospitalization [ 24 , 25 , 26 , 27 , 28 ]. Therefore, NLR correlated with post-CAP mortality better than traditional pneumonia scores (Pneumonia Severity Index, PSI; and Confusion, Urea, Respiratory rate and Blood pressure, aged 65 and older, CURB-65), WBC and CRP [ 24 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…Furthermore, 3-month likelihood of rehospitalization increases in parallel with NLR increase, with a rate >75% when NLR is >20 [ 24 ]. Other authors have observed that not only NLR value but also its incremental change can predict clinical instability and all-cause 30-day mortality [ 26 ]. Of note, NLR values on admission did not differ significantly between survivors and non-survivors [ 26 ], while those at 3–5 days differed and predicted more accurately 30-day mortality [ 27 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
See 2 more Smart Citations
“… 35 , 36 However, unfortunately, NLR was not statistically significant in the multivariable logistic model. In a recent study, Lee et al 37 found a significant association between the NLR value on day 4 with 30-day mortality and ICU admission whilst this value on day 1 was not associated significantly. NLR in our study was collected within 24 hours of admission.…”
Section: Discussionmentioning
confidence: 94%